THE ROLE OF INDONESIAN LABOR PLACEMENT AND PROTECTION BOARD (BNP2TKI) ON INDONESIAN LABOR (TKI) - Djatmiko, Agoes; Pudyastiwi, Elisabeth (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2019)
Establishment of the National Agency for the Placement and Protection of Indonesian Workers (BNP2TKI) To optimize the protection of migrant workers abroad which is more integrated, the government forms a national body whose duty is to protect Indonesian migrant workers abroad. A Non- Departmental government agency that is responsible to the President who is domiciled in the national capital, namely the National Agency for Placement and Protection of Indonesian Workers (BNP2TKI), whose functions are coordinating and integrated placement and protection of migrant workers abroad, with several tasks as follows: 1. Placing on the basis of a written agreement between the government and the government of the country that uses TKI or legal entity users in the destination country; 2. Providing services, coordinating, and supervising: documents, final departure briefing (PAP), problem solving, sources of funding, departure until repatriation, improvement of the quality of prospective migrant workers, information, quality of implementing TKI placement, and improving TKI welfare and his family. In accordance with the principle of international law, legal protection for citizens ceases when the citizens of that country cross the borders of the state jurisdiction. Protection of Indonesian workers abroad or in recipient countries is carried out in accordance with international law and applicable laws in the country.